Influence of tension cracks on moisture infiltration in loess slopes under high-intensity rainfall conditions - Xuancheng Ren; Weifeng Sun; Hengxing Lan; Han Bao; Langping Li; Shijie Liu; Changgen Yan; Xiaochan Wang; Zhouchen Li; Chaoyang Tian (Scientific Reports)
Abstract Loess slopes with steep gradients are particularly prone to vertical tension cracks at the crest, resulting from unloading and other factors. These cracks significantly affect the spatiotemporal distribution of moisture infiltration during rainfall, potentially leading to slope instability. This study investigates the impact of crest-tension cracks on moisture infiltration in loess slopes under extreme rainfall conditions, focusing on crack position, depth, and width. Soil moisture content and the dynamics of wetting fronts were monitored to assess how these tension cracks influence infiltration patterns. The results indicate that tension cracks at the slope crest act as preferential infiltration pathways, causing water retention within the cracks and forming a “U-shaped” preferential infiltration zone. The extent of this “U-shaped” wetting front is influenced by the crack’s width, depth, and proximity to the slope shoulder; wider, deeper cracks closer to the shoulder result in a more pronounced wetting front. Over time, as rainfall persists, the influence of preferential infiltration decreases, and the infiltration patterns of slopes with crest cracks begin to resemble those of homogeneous slopes. In both cases, wetting fronts exhibit intersecting patterns: one parallel to the slope crest and the other parallel to the slope surface. During the initial stages of rainfall, the migration speed of wetting fronts in slopes with crest-tension cracks was significantly higher than in homogeneous slopes. However, after prolonged rainfall, the migration speeds of wetting fronts in both scenarios converged. A strong linear correlation was observed between the average migration depth of the horizontal wetting front at the slope crest and the parallel wetting front on the slope surface, for both slope types. These findings deepen our understanding of moisture migration dynamics in loess slopes with crest-tension cracks, providing insights for developing effective slope hazard mitigation strategies.